Bending Property of Honeycombed 3D Woven Composites with Quadrilateral Cross Section. Issue 2 (March 2020) - Lyu, Lihua; Zhu, Liming; Cui, Jingrui; Guo, Jing; Ye, Fang
The delamination resistance and damage tolerance of traditional honeycomb composites are poor. To overcome these defects, 3D (three-dimensional) integrated woven composites of honeycomb structure were designed, and then manufactured using the vacuum assisted resin transfer molding process (VARTM), based on the 3D self-prepared fabrics used as reinforcements. The load-displacement curves, maximum bending load-velocity curves, and bar chart of energy absorption were determined experimentally and calculated by finite element simulation. The results showed good agreement between experimental and finite element simulation data. The correctness of the model was verified, so the model can be used to predict the mechanical properties of 3D integrated woven composites of honeycomb structure with quadrilateral cross section.